(untitled) (International Journal of Food and Nutritional Sciences, 2022)
History of any science gives an idea, how our ancestors solved the problems. Since history of mankind, wound continued to be one of the common suffering of which humans are constantly exposed. Surgical measures have been used in earliest time of civilization that is evident from the fossils of trephine human skulls and curved knives in the excavation. Human body has been constantly exposed to trauma, to extreme cold and heat, and also to various types of infection. Man is susceptible to wounding and that has led to think about healing from very early stage of human development. The art of surgery originated under the compelling effect of immediate crisis attempts to repair. The techniques of prevention of infection and its influence on wound are available in the scripture found during ancient civilization. The first dressings ever used were the leaves of trees, which were easily available from the surrounding. It appears that some of the ancients used tree resin to cover and protect the wound surface.